KERAGAAN KEDELAI (GLYCINE MAX.) GENERASI M1 HASIL MUTASI VARIETAS DEGA 1 DENGAN BEBERAPA KONSENTRASI ETHYL METHANE SULPHONATE - Bondan Fiarahman; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
To increase soybean productivity required some efforts as one is to develop new high yielding variety or improving existing varieties. To obtain and improved a variety, one need to obtain a population with high genetic variability in order to ease the selection of new suitable cultivars. In this study, we usedinduce mutations using chemical mutagen, ie, Ethyl Methane Sulphonate (EMS),to increase the variability. This research had been conducted in the Plant Breeding Laboratory and Experimental Garden of the Riau University. Seed of Dega-1 Variety were soaked by solution of EMS in buffer phosphate within several concentration ie, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm and 700 ppm. Seed then were washed with aquadest to cleand remaining EMS solution and than planted together by initial Dega-1 as control in the field experiment using a completely randomized design (RAL) withfour replications. Parameters observed were plant height, number of internodesthe age of flowering, age of harvest, number of pods per plant, number of filled podsper plant, number of seeds per plant, seed weight per plant, number ofseeds per pod and type of growth, flower color, and pod color. Population variancewere calculated byMicrosoft Excel software. The homogeneity ofthe variance was tested with HOV in accordance tothe procedures of theLevene’s test. The results showed that the induction of mutations with 200 ppm of EMSincreased genetic variance in M1 generation compare toDega 1 variety for most quantitative character, including plant height, number of pods per plant, number of filled podsper plant, number of seeds per plant, and seed weight per plant. Induce the mutation by EMS solution, on the other hand, didn’t change all qualitative character. Keywords:Induced Mutation, Ethyl Methane Sulphonate, Population Variance, Quantitative Traits, Qualitative Traits